Use of Old Coconut Water with Various Skim Concentrations of Milk as a Diluent for Kampong Chicken Semen - K. Khaeruddin; S. Srimaharani (Chalaza Journal of Animal Husbandry, 2019)
This study aims to determine the level of skim milk in the best coconut water that can maintain the quality of spermatozoa of native chickens during storage at 5oC. Semen was divided into five tubes (without diluents, diluents with skim milk levels 0%, 6%, 8% and 12, liquid Semen was then stored at 5oC. Observations of motility and viability were carried out at 0, 12, 24 hours, 36, and 48 hours. The results showed that the use of various diluents had a very significant effect (P 0.01) on the motility and viability of chicken spermatozoa at 12 hours of storage. The highest motility of spermatozoa was found in coconut milk diluent treatment with milk level skim 6%, and skim milk level 9% at 0 o'clock, 12 o'clock and 48 o'clock storage, while the highest motility at 24 o'clock and 36 o'clock was at treatment with skim milk level 6% Viability of spermatozoa at 0 o'clock does not differ between treatments but during storage, in general, the viability of spermatozoa can survive better in diluents with skim milk levels of 6% and 9% Conclusion of this study is coconut water Diluent with skim milk level of 6% and 9% can maintain the quality of chicken spermatozoa better during storage 48 hours at a temperature of 5oC.